Roles of Glial Cells in Sculpting Inhibitory Synapses and Neural Circuits - Um, Ji Won (Frontiers in Molecular Neuroscience, 2017)
Glial cells are essential for every aspect of normal neuronal development, synapse formation, and function in the central nervous system (CNS). Astrocytes secrete a variety of factors that regulate synaptic connectivity and circuit formation. Microglia also modulate synapse development through phagocytic activity. Most of the known actions of CNS glial cells are limited to roles at excitatory synapses. Nevertheless, studies have indicated that both astrocytes and microglia shape inhibitory synaptic connections through various mechanisms, including release of regulatory molecules, direct contact with synaptic terminals, and utilization of mediators in the extracellular matrix. This review summarizes recent investigations into the mechanisms underlying CNS glial cell-mediated inhibitory synapse development.